Survival of Microorganisms on Hospital Fabrics and Methods of Treatments (Review) - Idris, Fadl Elmoula Abd alla (Gezira Journal of Engineering and Applied Sciences, 2011)
Medical fabrics have been used widely in heath care units as well as in other sectors such as hotels restaurants and food industries. The hospital fabrics are considered as the host for bacteria and fungi, which they remain surviving on surface of fabrics for several weeks. This paper cites a review of the literature published on survival of microorganisms on hospital fabrics and methods of treatments applied to inhibit the reproduction of the microorganisms. The review shows that the times of persistence of microorganisms on fabrics were depending on type of microorganism, fabric and method of treatment.